Breaking barriers in establishing simulation in India–A collaborative approach by pediatric simulation training and research society (PediSTARS) - Jamalpuri, Vijayanand; Gunda, Ranjit Kumar; Ramachandra, Geethanjali; Thyagarajan, Sujatha; Shetty, Rakshay; Seethamraju, Rajasri R.; Nadkarni, Vinay M.; Shepherd, Michael (Frontiers in Pediatrics, 2022)
Simulation based training (SBT) plays a pivotal role in quality improvement and patient safety. Simulation is not only for training health care professionals but also an excellent tool for systems and facility changes which will potentially improve patient safety and ultimately outcomes. SBT is already established both as a training modality, and as a quality improvement tool in high income countries. It’s use in low and middle-income countries (LMIC), including India, however, is sporadic and variable because of multiple barriers. The barriers for establishment of simulation are lack of knowledge about benefits of simulation, psychological resistance, cost, and lack of trained faculty. PediSTARS (Pediatric Simulation Training and Research Society), a simulation society was founded in August 2013 to spread the simulation across India and thus improve the quality and safety of health care using SBT. In this article we discuss various barriers for healthcare simulation in India and also our attempts to overcome some of these barriers by collaborative practice.